Co-creating talent and human-centered organizations : organization development (OD) perspectives - Chinoperekweyi, Justine (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"As we dive deep into the humanistic paradigm - in society and in business, the models and narrative of business must change. The human-centric dynamic places people at the center of sustainable value creation. Therefore, leaders must shine the light on talent and people. The book 'Co-creating Talent and Human-Centered Organizations: Organization Development (OD) Perspectives' is an elaboration of the concepts to developing talent masters and build high-value organizations through cultivating enduring human capabilities and tapping into our collective capacities. Based on the OD field's fundamental values, the focus is, therefore, on enhancing the capacity of leaders to build resilient organizations. The book is informed by the realization that most organizational routines and boundaries inhibit and deplete enduring human capabilities and tendencies. Recognizing that organizations are open organizational systems, the book creates space for readers, leaders, managers, and OD professionals to continually reframe their cognitive and emotional frameworks towards high-value organizational cultures that would help co-create sustainable futures. Leveraging on the informal interpretations, impressions, insights and interventions of Organization Development (OD) 'tacit knowledge' and 'deep smarts', this book focuses on concepts targeted at charting the talent journey, identify cultural gaps in the workforce, modernize the learning & development architecture, and enhancing intentional change effort and purposeful enactment across all organizational members. The book leverages on Organization Development (OD) science, theory, practices, and values; and the role of Appreciative Leadership in developing talent in contemporary organizations. Whole System Thinking and co-creation of possibilities are central principles in this book. The book is informed by the increasing need for organizations to holistically prioritize the talent agenda and continuously drive competitiveness and performance through workforce optimization approaches. This is necessitated by the emergence of multi-generational workforce, the pervasive impact of technology, increasing talent mobility, shifts towards increased reliance on virtual teams, and the effects of globalization on the talent landscape"--